The Growth of the Federal Crop Insurance Program, 2010–22 - Glauber, Joseph W. (American Enterprise Institute, 2023)
Key Points: Two major trends have defined the federal crop insurance program over the past 12 years: the replacement of farm yield–based insurance with farm revenue–based products and the explosion of area- and index-based insurance for pasture, rangeland, and forage crops. Though still relatively small, enrollment in two relatively new products has grown over the past decade: supplemental insurance based on county yields designed to cover deductibles associated with farm yield–based policies and livestock insurance. Thus, enrolled acreage and total premiums for crop insurance hit record highs in 2022, with continued enrollment growth in area- and index-based policies expected in 2023.